Structural, Magnetic and Dielectric Properties of the Novel Magnetic Spinel Compounds zncosno4 and zncotio4 - Ruiz-Leon, D; Ruiz-Leon, D (Elsevier Ltd, 2018)
The transparent semiconductor Zn2SnO4 with cubic spinel structure and the isostructural Zn2TiO4 have been magnetically doped with Co2+. ZnCoSnO4 and ZnCoTiO4 exhibit ferrimagnetism below TN ≈ 13 K and TN ≈ 17 K. Ferrimagnetic moments are evident in M vs H curves below TN by small hysteresis. Fits to strictly linear Curie-Weiss plots above TN give μeff ≈ 4.86 μB and ≈4.91 μB for ZnCoSnO4 and ZnCoTiO4, above theoretical predictions. Impedance spectroscopy data from sintered ceramic can be fitted with a standard equivalent circuit model based on two RC elements for bulk and GB areas. The relative dielectric permittivity of the bulk is ≈20 and ≈30 for Zn2SnO4 and Zn2TiO4. The semiconducting ZnCoSnO4 and ZnCoTiO4ceramics exhibit bulk resistivity of ≈1 106 Ω cm and ≈1 105 Ω cm at 560 K (287 °C), and bulk activation energies of EA ≈ 1.2 eV and 1.1 eV. © 2018 Elsevier Ltd